Growth and major histocompatibility antigen expression regulation by IL-4, interferon-gamma (IFN-gamma) and tumour necrosis factor-alpha (TNF-alpha) on human renal cell carcinoma. - Hillman, G G (1994)
We have recently shown that human renal cell carcinoma (RCC) tumour lines express high-affinity IL-4 receptors. Binding of IL-4 to RCC cells induced a growth inhibition in the range of 20-68%. To enhance the growth inhibitory effect of IL-4, we have tested the effects of two additional cytokines capable of directly affecting tumour cell growth. IFN-gamma caused a significant inhibition of RCC tumour cell growth (up to 70%) in a dose-dependent manner, whereas the effect of TNF-alpha was more limited (0-20% inhibition). The addition of IL-4 to IFN-gamma on RCC cells sensitive to IL-4 induced a greater inhibition of cell growth than that seen with each cytokine alone. IL-4 and IFN-gamma rendered RCC cells more responsive to the inhibitory effect mediated by TNF-alpha. The combination of TNF-alpha with IL-4 and IFN-gamma induced an optimal growth inhibition (up to 90-98%) of RCC cells. In addition to a direct anti-proliferative effect, we have demonstrated that these cytokines can also enhance the expression of MHC antigens on the surface of RCC tumour cell lines which may render the cells more immunogenic. All RCC lines tested expressed class I antigens, but not class II antigens. IFN-gamma induced class II expression and up-regulated the expression of class I antigens on RCC cells. Class II antigen expression was detectable following 48 h incubation, and greater after 72 h with IFN-gamma. IL-4 minimally affected class I expression, whereas TNF-alpha up-regulated class I antigen expression. IL-4 or TNF-alpha did not induce class II expression. The combination of the three cytokines slightly augmented the up-regulation of class I and class II antigens observed with IFN-gamma alone. These observations confirm the direct interaction of IL-4, IFN-gamma and TNF-alpha with RCC tumour cells, both at the level of growth regulation and MHC antigen expression, and suggest a therapeutic potential of the combination of the three cytokines for renal cell carcinoma.